2016
DOI: 10.1155/2016/1503206
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate/Sphingosine-1-Phosphate Receptor 2 Axis Can Promote Mouse and Human Primary Mast Cell Angiogenic Potential through Upregulation of Vascular Endothelial Growth Factor-A and Matrix Metalloproteinase-2

Abstract: Mast cells (MC) are present in most vascularized tissues around the vasculature likely exerting immunomodulatory functions. Endowed with diverse mediators, resident MC represent first-line fine-tuners of local microenvironment. Sphingosine-1-phosphate (S1P) functions as a pluripotent signaling sphingolipid metabolite in health and disease. S1P formation occurs at low levels in resting MC and is upregulated upon activation. Its export can result in type 2 S1P receptor- (S1PR2-) mediated stimulation of MC, furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…MC can be activated by S1P, an influential sphingolipid metabolite resulting from the phosphorylation of its precursor sphingosine by SphK . Quantitative lipid analysis using lipidomics mass spectrometry revealed that S1P was significantly increased in mouse skin after 1 exposure to OVA, compared to controls (Figure F and Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC can be activated by S1P, an influential sphingolipid metabolite resulting from the phosphorylation of its precursor sphingosine by SphK . Quantitative lipid analysis using lipidomics mass spectrometry revealed that S1P was significantly increased in mouse skin after 1 exposure to OVA, compared to controls (Figure F and Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that MC‐derived S1P, produced by sphingosine kinase (SphK), can be exported out to amplify MC cytokine/chemokine production and regulate cell trafficking . S1P can also activate MC independently of the canonical IgE/FcεRI pathway …”
Section: Introductionmentioning
confidence: 99%
“…Mast cells may differentiate into two subsets depending upon the tissue they populate and the microenvironmental conditions, as defined by the protease repertoire harbored within cytoplasmic granules: connective tissue or serosal MC express tryptase and chymase, whereas mucosal MC are single positive for tryptase ( 120 ). Importantly, MC-derived proteases can activate matrix metalloproteinases (MMP) that are critical to tumor growth and metastasis, and we recently reported that S1P-mediated MC activation triggered substantial release of MMP and pro-angiogenic VEGF ( 131 ). We and others have shown that MC can produce S1P ( 3 , 132 ).…”
Section: S1p As a Modulator Of The Tumor Microenvironmentmentioning
confidence: 99%
“…The MC/S1P/S1PR2 axis was recently shown to be crucial for propagating early inflammatory responses in murine models of pulmonary and cutaneous allergic responses . Additionally, S1PR2 ligation leads to production of tissue remodeling matrix metalloproteinase‐2 (MMP2) and vascular endothelial growth factor (VEGF)‐α from human MCs . Eosinophils express S1PR1, 3, 4, and 5 and can therefore be recruited to inflamed tissues by MCs and other S1P‐producing cells.…”
Section: Cell Surface Receptorsmentioning
confidence: 99%
“…154,155 Additionally, S1PR2 ligation leads to production of tissue remodeling matrix metalloproteinase-2 (MMP2) and vascular endothelial growth factor (VEGF)α from human MCs. 161 Eosinophils express S1PR1, 3, 4, and 5 and can therefore be recruited to inflamed tissues by MCs and other S1P-producing cells. Eosinophil chemotaxis toward S1P can be abrogated in the presence of the pharmacological S1P receptor antagonist FTY-720, which has significant affinity for all S1PR except S1PR2.…”
Section: Whilementioning
confidence: 99%